Domestic sewage irrigation on dynamics of nutrients and heavy metals in soil and wheat (Triticum aestivum L.) production - S. R. Salakinkop; C. S. Hunshal (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Background Evaluation of urban sewage for its feasibility and potentiality as sources of irrigation water and plant nutrient is need of the hour. In this context, a field experiment was laid out in splitâsplit plot design with three replications. Main plots constituted two types of lands (fields irrigated with sewage and bore well water since 1992). Subplots were allotted with three sources of irrigation which consisted of sewage water alone, bore well water alone (good water) and conjunction of sewage and bore well water. And sub-subplot constituted of four fertilizer levels (no fertilizer, 50 % recommended rate of fertilizer (RRF), 75 % RRF and 100 % RRF. Results Crop growth in terms of photosynthesis, net assimilation rate and dry matter production significantly increased in sewage-irrigated land compared to bore wellirrigated land. Similarly, significantly higher wheat grain yield (4370 kg ha-1 ), protein (12.88 %) and dry gluten (9.22 %) were obtained in field irrigated with sewage water compared to bore well-irrigated land. Sources of irrigation also differed significantly producing higher grain yield (4,100 kg ha-1 ), protein (12.81 %), dry gluten (8.97 %) in sewage irrigation compared to bore well water irrigation. Enhanced activity of dehydrogenase and phosphatase enzymes and organic carbon in sewage-irrigated field contributed more to available nutrient pool of soil. Pooled results of 2 years revealed that wheat roots accumulated significantly higher amount of Cr, Ni, Pb and Cd in sewage-irrigated land compared to bore well-irrigated land. The same trend was noticed in stem with respect to Cr and Ni. In general, concentration of heavy metals was higher in root followed by stem and lower in grain. The Pb concentration in plant parts (root, stem and grain) was not influenced by land type and sources of irrigation. None of the treatments did show accumulation of these heavy metals in wheat plant parts more than normal range found in food plants. The values of these metals were below the recommended maximum tolerable levels proposed by the Joint FAO/WHO Expert Committee on Food Additives, Summary and conclusions. In: 53rd Meeting, Rome, (1999). Conclusion Increased wheat grain yield in sewage-irrigated land compared to bore well-irrigated land was attributed to increased soil fertility that was a result of continuous sewage irrigation. Long-term irrigation of farm lands with wastewater leads to contamination of soil and plant system with heavy metals in the study area. Wastewater-irrigated soil showed significant (p.05, p.01) accumulation of heavy metals compared to the freshwater-irrigated soil indicating concern of their increased absorption in wheat plant. The accumulation of heavy metals in wheat plant was in the order of roots [- stems [grains. However, all these heavy metals in plant system were lower than the recommended threshold level.